Religious and philosophical libraries of East Siberian Buddhists: Tibetan «pocket» books - A. A. Bazarov; D. L. Dorzhieva; D. Yu. Munkozhapov; S. M. Naidanova (Библиосфера, 2018)
The problem of studying private book collections of the Siberian peoples is the most urgent in understanding the cultural diversity of Russia. In this context, the book culture of East Siberia Buddhists is of interest. The article objective is to analyze the book repertoire of Buddhists private libraries. Analysis of this repertoire allows us to reconstruct not only its structure but the level of book culture among local Buddhists in the XIX-XX centuries as well. The material for reconstruction is a collection of small-format Tibetan-language publications (SFTP) from the collections of the Center for Oriental Manuscripts and Xylographs of the Institute of Mongolian, Buddhist and Tibetan Studies of the Siberian Branch of the Russian Academy of Sciences. This collection is an aggregation of numerous private libraries (PLs), widely distributed among the Buddhists of Transbaikalia and Prebaikalia. Books from the PLs are related to different areas of Buddhist knowledge: religious doctrine, philosophy, philology, astrology, medicine. The largest fields are religious doctrine and philosophy. The research results show that due to the texts of «Diamond Sutra» and Pramanavartika, it is possible to reconstruct not only the repertoire of Buddhists PLs in East Siberia, but elements of everyday Buddhist culture. In this culture, religious-doctrinal texts were involved in the daily ritual activity of laypersons, and philosophical texts in the system of monastic education. The texts ratio of Pramanavartika (5 copies) and «Diamond Sutra» (48 copies) available in SFTP is about 10%. This parameter can indicate both the approximate correlation of religious-doctrinal books to philosophical ones in this collection, and the real ratio of monks and laity number in the pre-revolutionary period in Buryatia. Thus, it can be argued that the «pocket» religious and philosophical libraries of Buddhists (each bundle of the studies collection) is the most interesting source of various scientific information on the book realities of Buddhist culture in East Siberia.